THE SUBSURFACE STRUCTURE INVESTIGATION OF DIENG PLATEUAU, CENTRAL JAVA, INDONESIA BY USING THE MAGNETOTELLURIC DATA - Gaffar, Eddy Zulkarnaini (Teknologi Indonesia, 2017)
Dieng Plateau area has a geothermal energy power station with a capacity of 60 MW. Research Center for Geotechnology, Indonesian Institute of Sciences (LIPI) tried to expand the productive areas in Dieng to other prospective areas around Dieng Plateau using the Magnetotelluric method. Magnetotelluric measurement was done by taking path stretching from east to west and from north to south comprising of 24 locations, each with a distance of 2 to 4 km. The tools used are Phoennix MTU-5A by using two kinds of coils, namely MTC-30 for high frequency 1,000–10.000 Hz and MTC-50 for low frequencies from 0.00001 to 400 Hz. Three lines for the two-dimensional cross section were made. From the three cross-sections, there are rocks with resistivity value of ≤32 Ωm interpreted as soft rock or alteration rock and Dieng volcanic rocks as cap rock. Under the cap rock, there are rocks with resistivity value between 64–1.000 Ωm with thickness of about 1,000–2,000 meters which are interpreted as volcanic clastic rocks and lava from Jembangan, Damar, and Ligung Formation as reservoir rocks. In the very bottom rock, there are rocks with resistivity value of ≥1,000 Ωm interpreted as igneous rock which still contain heat from the Quaternary intrusion that are not exposed at the surface and the Kumbang Formation consists of andesite and basalt lava. The developing structure is classified as normal fault structures as seen on all of the line that make the reservoir trap better. On the western region, namely Wanayasa area and the north west area of Mangunan, there were rocks with the same system and structure as found on the eastern area (Dieng prospect area). Therefore, in addition to current productive Dieng area, there are also other prospective areas in Wanayasa and Mangunan area.